A influência da abertura comercial, capital humano e da concentração de renda na produtividade dos estados brasileiros - Miranda, Eduardo Pádua Jardim de (2004)
This work looks for to investigate the influence of the degree of the commercial opening, the level of human capital and the concentration of income on the total productivity of the factors (TFP) of 21 Brazilian states in the period of 1986 the 1995. Using the methodology of the accounting of the growth of Solow (1956) the TFP was esteem from a function of Cobb-Douglas production using given in panel. It was verified that those States that possess greater level of human capital and bigger degree of integration to the international trade tend to present a bigger level of the TFP, whereas the income concentration possesss an adverse influence.